Russia–Ukraine conflict and its impact on global inflation: an event study-based approach - Maurya, Prince Kumar; Bansal, Rohit; Mishra, Anand Kumar (Journal of economic studies (Bradford), 2023)
PurposeThis study investigates how the conflict between Russia and Ukraine impacts global inflation.Design/methodology/approachThe study uses monthly consumer price index (CPI) data from 60 countries for 30 months, from January 2020 to June 2022. An event study methodology has been employed to check abnormal variation in the CPI, after classifying country-specific monthly data into nine groups.FindingsThe outcome revealed that Russia's full-scale invasion of Ukraine triggered inflation globally. However, the severity of inflation in the sample countries is determined by their geographical proximity and trading activity with the countries in conflict. A significant rise in inflation was observed among major European economies during the invasion. As the war continues, the increase in the price of essential commodities is evident worldwide.Originality/valueThe war literature till now has concentrated on stock markets, energy markets, exchange rates and precious metals. Since no previous research has attempted to quantify the abnormal effect of the war on domestic and global inflation, the current study will shed much-needed light on the subject.